Diseño de un horno de templado y termoendurecido de vidrio plano. - Guevara Palacios, Christian Alexander (2016)
This research deals with the design of a furnace to hardened and toughened flat glass, the same that was designed with four main elements: entry table, heating chamber, cooling chamberand exit table. The furnace operates with electrical resistances up to 43.5 kW. First, we proceeded to establish the maximum dimensions of the load and its thickness, the range of operating temperatures was determined using the method of weighted criteria was determined that the best alternative for the design of the oven corresponds to a furnace batch, electrical resistance, horizontal type with cargo configuration. The tempering process is complemented by a rapid cooling of the load by an array of compressed air nozzles. Once the thermal, pneumatic and electrical characteristics are stablished a 3D design was done in Solid Works software, also the user interface was developed in Labview software and the process simulation is performed by controlling the temperature and location of the load along the cameras.